2018
DOI: 10.1590/0100-29452018178
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and exportation of nutrients by yellow Passion fruit cv. IAC 275

Abstract: The mineral nutrition is essential to increase yield and fruit quality of passion fruit. There is no information of nutrient accumulation throughout the production cycle. Thus, in order to assist in the correct nutrients supply and update the recommendations, studies involving cultivars and cultivation techniques are necessary. The aim of this study was to evaluate the plant growth, the nutrient accumulation and the exportation in plants of yellow passion fruit cv. IAC 275. The experimental design was a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…The plants originated from seedlings with root systems between 100 cm and 125 cm presented higher yields in harvests 1 and 2, as well as total yield ( Figure 2). This may be related to the greater height and base diameter of these plants when taken to the field (Figure 1), since they possess a shorter juvenile period and higher capacity of water absorption due to the greater soil volume explored by the roots (Beyer et al, 2016;Mattar et al, 2018;Souza et al, 2008). DAT), which demand 954.98 mm (Silva & Klar, 2002), as a consequence of the higher accumulation of leaf area and fruit production.…”
Section: Resultsmentioning
confidence: 99%
“…The plants originated from seedlings with root systems between 100 cm and 125 cm presented higher yields in harvests 1 and 2, as well as total yield ( Figure 2). This may be related to the greater height and base diameter of these plants when taken to the field (Figure 1), since they possess a shorter juvenile period and higher capacity of water absorption due to the greater soil volume explored by the roots (Beyer et al, 2016;Mattar et al, 2018;Souza et al, 2008). DAT), which demand 954.98 mm (Silva & Klar, 2002), as a consequence of the higher accumulation of leaf area and fruit production.…”
Section: Resultsmentioning
confidence: 99%
“…The seedlings transplantation to the field occurred in 10/11/2017, 224 days after sowing, when the coverage fertilizations with N (ammonium nitrate source, 32 % of N and 1% of K 2 O) started, for the application of the treatments. N doses were applied between November/17 and May/18 and the relative quantities varied according to the need of the crop (MATTAR et al, 2018). These were 10; 22.5; 22.5; 22.5; 22.5% of the total N at 36; 97; 134; 167; 218 days after transplantation (DAT) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, although nitrogen (N) is the most extracted nutrient and the second most exported (HAAG et al, 1973;MATTAR et al, 2018) the recommended N amount for the crop varies between 94 and 235 kg ha -1 year -1 (RIPADO, 2010;MIYAKE et al, 2018). In addition, studies showed variable responses on N effect on fruit quality as well as nutritional studies in area with the presence of HFV, the performance evaluation of advanced seedlings in the field on N doses effect and its correlation with productivity are scarce (AULAR et al, 2014;MIYAKE et al, 2018;BERTANI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…bras., Brasília, v.37, n.2, April-June 2019 S tudies on accumulation and export of nutrients show quantity and period of high gains of these nutrients as function of plant age, indicating when nutrient addition is necessary. Thus, these are important tools for management and fertilization of crops as also helping update existing recommendations (Furlani & Purquerio, 2010;Purquerio et al, 2016;Moraes et al, 2018;Mattar et al, 2018).…”
Section: Scientific Communicationmentioning
confidence: 99%